Cathepsin Protease Inhibition Reduces Endometriosis Lesion Establishment. (May 2016) - Porter, Kristi M.; Wieser, Friedrich A.; Wilder, Catera L.; Sidell, Neil; Platt, Manu O.
Endometriosis is a gynecologic disease characterized by the ectopic presence of endometrial tissue on organs within the peritoneal cavity, causing debilitating abdominal pain and infertility. Current treatments alleviate moderate pain symptoms associated with the disorder but exhibit limited ability to prevent new or recurring lesion establishment and growth. Retrograde menstruation has been implicated for introducing endometrial tissue into the peritoneal cavity, but molecular mechanisms underlying attachment and invasion are not fully understood. We hypothesize that cysteine cathepsins, a group of powerful extracellular matrix proteases, facilitate endometrial tissue invasion and endometriosis lesion establishment in the peritoneal wall and inhibiting this activity would decrease endometriosis lesion implantation. To test this, we used an immunocompetent endometriosis mouse model and found that endometriotic lesions exhibited a greater than 5-fold increase in active cathepsins compared to tissue from peritoneal wall or eutopic endometrium, with cathepsins L and K specifically implicated. Human endometriosis lesions also exhibited greater cathepsin activity than adjacent peritoneum tissue, supporting the mouse results. Finally, we tested the hypothesis that inhibiting cathepsin activity could block endometriosis lesion attachment and implantation in vivo. Intraperitoneal injection of the broad cysteine cathepsin inhibitor, E-64, significantly reduced the number of attached endometriosis lesions in our murine model compared to vehicle-treated controls demonstrating that cathepsin proteases contribute to endometriosis lesion establishment, and their inhibition may provide a novel, nonhormonal therapy for endometriosis.